Dermatosis as the initial presentation of gastric cancer: two cases - Ge, Wei; Teng, Bu-Wei; Yu, De-Cai; Chen, Gang; Zheng, Li-Ming; Ding, Yi-Tao (Chinese Journal of Cancer Research; Vol 26, No 5 (October 31, 2014): Chinese Journal of Cancer Research, 2014)
Paraneoplastic dermatoses are known to be certain dermatosis related with tumor. The common paraneoplastic dermatoses are acanthosis nigricans, acquired ichthyosis, dermatomyositis, erythroderma, and so on. Here we report two cases of paraneoplastic dermatoses associated with gastric cancer. One case was a 57-year-old man with dermatomyositis and proved to be associated with gastric cancer through stomachoscopy. The other was a 66-year-old man with erythroderma and proved to be associated with gastric cancer through stomachoscopy. Both cases were treated with radical total gastrectomy with lymphadenectomy (D2) and esophagojejunostomy of Roux-en-Y. The skin symptom of both cases had improved a lot but still existed after operation. Paraneoplastic dermatoses can be seen as the early manifestation of visceral carcinomas. As a result, gastric cancers should be excluded in the patients with paraneoplastic dermatoses.